Study of allelic diversity of the Rf1 gene in grain sorghum samples - N. N. Vozhzhova; О. S. Zhogaleva; V. V. Kovtunov (Зерновое хозяйство России)
Grain sorghum (Sorghum bicolor (L.) Moench) is one of the important grain crops in world production. In order to develop valuable heterotic hybrid lines, breeders use cytoplasmic male sterility (CMS), which is mainly based on the A1 (milo) cytoplasm in Russia. This type of CMS is controlled by several genes, one of which is the Rf1 gene. The purpose of the current work was to study the allelic diversity of the Rf1 gene in breeding and collection grain sorghum samples. Genomic DNA of grain sorghum was isolated by the CTAB method from young sprouts. The quantity and quality of DNA were estimated by a spectrophotometer. For PCR analysis, there was used a specific molecular marker Xtxp18, which established a wide allelic diversity of the 30 grain sorghum samples studied. The comparison of the results of molecular analysis and the fertility level of samples in field conditions has shown that the greatest share in the fertility formation belonged to the alleles Rf1j (30 %) and Rf1d (32 %) in the group of fertility restorer samples (B); and the alleles Rf1a (23.33 %), Rf1d (23.33 %) and Rf1c (15 %) in the group of fertile plants not involved in crossing. Alleles Rf1a, Rf1d and Rf1c had a high percentage of association with field fertility of the samples (similar to the effect of the Rf1j allele), and therefore can be used in grain sorghum breeding aimed at developing fertility restorer lines. In order to breed grain sorghum to develop fertility restorer lines, it can be recommended to use samples with the Rf1j allele (associated with fertility), in which it was revealed to a greater extent, and the samples themselves belonged to the group of fertility restorers 21/22, 22/22, 23/22, 24/22 and 27/22. In order to develop sterile lines, there can be used grain sorghum genotypes with the Rf1e allele (associated with sterility) 7/22, 8/22, 9/22 and ZSK 1497/21 after confirming their fixation ability in field conditions.